Geochronology and geochemistry of the Thirsty Creek Norite, Westland, New Zealand. Issue 3 (3rd July 2019) - Kylborg, Sarah Estela; Waight, Tod; van der Meer, Quinten
ABSTRACT: Thirsty Creek Norite is a small, undeformed, mafic intrusion intruding gneisses of the Granite Hill Complex in the Buller Terrane. An age of 107.1 ± 4.1 Ma has been obtained using Rb-Sr geochronology. A relatively high MSWD of 4.5 is attributed to sericitization and alteration of plagioclase. This date is consistent with other ages for the timing of high-grade metamorphism in the Granite Hill Complex and may represent a metamorphic age, thus providing a minimum age for metamorphism and emplacement of the norite. However, the relatively undeformed nature of the Thirsty Creek Norite suggests it may postdate metamorphism and we speculate that the date could represent a crystallisation age which is contemporaneous with Rahu Suite granitic magmatism in the adjacent Hohonu Batholith. Several geochemical characteristics, including overlapping initial Sr and Nd isotope compositions, suggest the Thirsty Creek Norite could be a relatively mafic yet contaminated melt that is petrogenetically related to Rahu Suite magmatism. Overlaps in the isotopic compositions of the Thirsty Creek Norite and Rahu Suite granitoids therefore imply that any mafic components involved during granitic magmatism must have had relatively enriched isotopic compositions, and that evolution to more felsic compositions occurred without significant interactions with upper crustal components.